Morphobiological description of different ages young Sattar snowtrout Schizopyge curvifrons from the Arysandy River (the Syrdarya River watershed) (Eurasian Journal of Ecology, 2016)
Fish grow is one of the important indicator of the state of environment. Morphobilolgical characteristics of different ages young Sattar snowtrout Schizopyge curvifrons Heckel, 1838 from the Arysandy River (the Syrdarya River watershed) were investigated in connection with problems of sustainable use of water and natural biodiversity conservation in the region. The Sattar snowtrout inhabits there together with other 8 indigenous and 3 alien fish species. Observed temp of length and weight grow of the Sattar snowtrout from the Arystandy River corresponds to the known data for“dwarf” or “spring” form of that species from the Talas River watershed. Big individual differences among fishes of each age reflect wide heterogeneity of living conditions exists in small rivers of the Syrdarya River watershed.
Keywords: morphobiological; grow; condition; asymmetry; environment